Comparison Of Achievement Sport Systems Between Indonesia And China - Muhammad Reza Aziz Prasetya (Universitas Ma'arif Nahdlatul Ulama Kebumen, 2021)
Sport as a model of human creativity is a form of physical activity that has very complex dimensions, which undergo a systematic process in the form of all activities or efforts that can encourage, arouse, develop and foster one's physical and spiritual potential. as individuals or members of society. in the form of games, competitions/contests, and intensive physical activities to obtain recreation, victory, and peak potential. Sport is currently a trend or lifestyle for some of the general public, even to the point of becoming a basic need in life. National development through the development of sports in Indonesia in this reform era has become a strategic vehicle, especially improving the quality of human resources, as well as the formation of the character and character of the nation, in this paper many factors play a role in success in the field of sports, one of which the author wants to examine the differences and similarities between the performance sports system that runs in Indonesia and China. This study aims to compare the development of achievement sports systems carried out in Indonesia and China in order to improve the quality and competence of sports. This study uses a qualitative descriptive method with data collection techniques through documentation studies. The results of this study conclude that the government's contribution is needed in preparing winning strategies, training facilities, increasing competition opportunities and increasing resources that can be assisted by a team of academics and researchers from universities to find new techniques in training to support the maximum use of sport science. Keywords: achievement sports system, Indonesia, China.